Are Australian regulatory codes adequate in scope to protect youth from alcohol advertising?. (15th September 2020) - Jongenelis, Michelle I.; Pierce, Hannah; Keric, Danica; Stafford, Julia; Jongenelis, Gregory; Pettigrew, Simone
Abstract: Issue addressed: Exposure to alcohol advertising has been found to be associated with more positive attitudes toward alcohol and heavier drinking among youth. Appropriate regulation of alcohol advertising is thus crucial for reducing use among members of this population group. To assist policy makers in their alcohol control efforts, this study explored the scope of Australian alcohol advertising codes and the extent to which they address issues relating to youth exposure. Methods: Two researchers assessed 628 unique alcohol advertisements against youth‐related provisions of the Alcohol Advertising Review Board (AARB) Code and Alcohol Beverages Advertising Code (ABAC). A third researcher resolved discrepancies. The ads sampled were those that had been the subject of formal complaints to the AARB. Results: Most (94%) ads were assessed as violating at least one of the AARB Code provisions relating to youth, while 36% were found to violate at least one of the ABAC youth provisions. The most frequently violated AARB Code provision related to placement, with 88% of ads located in places or broadcast at times where young people were likely to be exposed. The most frequently violated ABAC provision related to appeal to minors (33%). Conclusions: Results indicate that self‐regulation is an ineffective means of protecting youth from alcohol advertising, with the ABAC failing to capture many ads featuring content that appeals to youth. So What?: Greater efforts are required to protect youth from alcohol advertising. Findings from the present study reinforce calls for mandatory, evidence‐based regulation that is administered independently of the alcohol industry. Summary: An analysis of 628 unique alcohol advertisements found that the vast majority were in violation of the AARB Code's youth‐related provisions whereas substantially fewer were in violation of the ABAC, supporting arguments that self‐regulation is an ineffective means of protecting youth from alcohol advertising.